Connecting Places, Connecting People A Paradigm for Urban Living in the 21st Century - Tiwari, Reena (Routledge, 2018)
Connecting Places, Connecting People offers a new paradigm for place making by reordering urban planning principles from prioritizing movement of vehicles to focusing on places and the people who live in them.